Penganiayaan Dan Perlakuan Yang Tidak Semestinya Terhadap Anak - Randi, Randi; Khusnul Hatimah, Ani; Safrina, Nabilla; Rahmansyah, Rahmansyah (Yayasan Darussalam Bengkulu, 2023)
Because of their status as relatively helpless members of the family system, children are most at risk of being subjected to the aggressive behavior of their parents or other older family members. As Tedeschi and Felson (1994, p. 287) have noted,